Evaluation of enzymatic and non‐enzymatic antioxidants in seminal plasma of men with genitourinary infections, varicocele and idiopathic infertility. (29th March 2016) - Micheli, L.; Cerretani, D.; Collodel, G.; Menchiari, A.; Moltoni, L.; Fiaschi, A. I.; Moretti, E.
Summary: This study was aimed to assess the antioxidant enzymatic and non‐enzymatic compounds in semen of infertile men. Seventy‐four infertile patients were grouped according to their clinical diagnosis: genitourinary infection, varicocele, idiopathic infertility. Semen samples of fertile men represent the control. Semen characteristics were evaluated by light and transmission electron microscopy (TEM). TEM data was quantified with a mathematical formula, which provides numerical scores. Spectrophotometric and HPLC methods were used to measure the amount of reduced (GSH), oxidised glutathione (GSSG), ascorbic acid (AA) and malondialdehyde (MDA, marker of lipid peroxidation) and the activity of glutathione reductase, catalase (CAT), glutathione peroxidase. Infertile groups showed significantly decreased values of sperm parameters vs. controls. In infection and varicocele groups, the seminal MDA levels were significantly increased when compared to controls ( p  < 0.001), indicating an alteration of oxidative status and a peroxidative damage. In infection and varicocele groups, AA levels were reduced ( p  < 0.05) vs. control; in the varicocele group, the GSH levels were also decreased ( p  < 0.05). Significantly higher CAT activity was observed in infection and varicocele groups vs. fertile men ( p  < 0.001 and p  < 0.05 respectively). The GSH/GSSG ratio was significantly decreased in varicocele and idiopathic infertility groups vs. control ( p  < 0.01). The study of the alteration of a single parameter of oxidative stress or of the antioxidant system may not have a relevant clinical value to estimate male fertilising potential and the background of infertility causes, since complex and multifactorial mechanisms are involved in different pathologies. In our study, each pathology is characterised by a definite pattern of markers such as MDA and enzymatic and non‐enzymatic antioxidant compounds. In the different pathologies related to infertility, the identification of the complex of involved parameters could be useful in the diagnosis, prognosis and in the choice of a possible treatment such as specific antioxidant supplements.